Hydrothermal alkaline treatment of lignocellulosic biomass for microcrystalline cellulose generation at subcritical water - Siti Machmudah; Wahyudiono; Prida Novarita Trisanti; Heru Setyawan; Suci Madhania; Kriyo Sambodho; Sugeng Winardi; Tadafumi Adschiri; Motonobu Goto (South African Journal of Chemical Engineering)
Like lignocellulosic biomass, wood waste sawdust is rich in cellulose and can potentially be used as a source of microcrystalline cellulose (MCC) production via removal of hemicellulose and lignin constituents. Under hydrothermal alkaline treatment (100 to 140 °C), the breaking in the linkages of lignin and hemicellulose groups may happen, resulting in the solid residue, which is known as a cellulose-rich solid product. Results of FTIR analysis indicated that the removal of non-cellulosic constituents improved with increasing operating temperature and/or the prolonged treatment time. The XRD diffractogram pattern proved that improving the operating parameters (temperature and/or time) may also improve the crystallinity index of the solid product. On the contrary, the yield of the solid product decreases with increasing operating temperature and/or the prolonged treatment time.